Network game (Literati) / Chung Mei Kuen - Chung, Mei Kuen (2003)
This thesis steps towards developing a networked game, Literati game system that supporting two players at one time. The main aspect of this thesis is to produce a networked gaming system, which process players. requested to play the game and enabling users to play the graphical game with people through the network. The algorithm design and implementation method must not only be workable, but also highly efficient in terms of execution speed and response time. With the powerful networking features of Java applet, it is expected that this project would produce a real game engine. Multithreading is an important aspect of network game. Therefore, efficient and robust servers that process separate client connections in separate threads are needed. Java applet is a well-known and widely used example of mobile code (a variation on the traditional client-server model). It should be an interesting, time and value worth topic to research on. By using Java applet, it will give a good interactive response since it does not suffer from the delays or variability of bandwidth associated with network connection. The possible applications of multimedia-networked system are endless, as the demand to support interactive communication among groups of users has increased significantly. The category of networking would serves to be a small foundation from which to base the future scenario of other reliable multicast and real time web based gaming system.